The Role of Probiotics in Combating Antibiotic-Resistant Bacteria - Chinedu, Otali Cyril; Deborah , Onose Efetobore; Uche, Okoye Simonpeter (American Journal of Bioscience and Clinical Integrity, 2025)
Antibiotic resistance is an escalating global health crisis that undermines the efficacy of conventional antimicrobial therapies. As traditional antibiotics become less effective against resistant pathogens, alternative approaches such as probiotics have gained attention for their potential role in mitigating antimicrobial resistance. Probiotics defined as live microorganisms that confer health benefits to the host exhibit various mechanisms that make them promising candidates in this context. These include competitive exclusion of pathogens, enhancement of the host’s immune response, production of antimicrobial substances, and modulation of gut microbiota. This study explores the current literature on the use of probiotics against antibiotic-resistant bacteria, examining both their direct and indirect antimicrobial activities. Mechanistic insights reveal that probiotics may disrupt quorum sensing, produce bacteriocins and organic acids, and strengthen epithelial barriers, thereby inhibiting the colonization and proliferation of resistant microbes. Despite their promise, the clinical translation of probiotics faces several challenges, such as strain specificity, inconsistent efficacy, safety concerns in immunocompromised individuals, and lack of regulatory standardization. The review concludes that while probiotics are not a standalone solution, they offer a complementary strategy in the global effort to curb antibiotic resistance. Recommendations include advancing strain-specific research, conducting well-designed clinical trials, enhancing regulatory oversight, and integrating probiotics into antimicrobial stewardship programs. With rigorous scientific validation and strategic implementation, probiotics may serve as an effective tool in preserving the efficacy of current antibiotics and promoting sustainable healthcare practices.